Eco-Friendly Cellular Lightweight Concrete Partition Walls Using Sandblasting Waste for Seismic Mitigation - Cahyono, Luqman; Dermawan, Denny; Pratiwi, Wiwik Dwi; Widiana, Dika Rahayu; Utomo, Agung Prasetyo; Fahmi, M. Rizal; Rosalina, Amanda; Suroidah, Eva Nur; Carina, Annisa; Oktaviastuti, Blima (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
The increasing demand for efficient construction materials has driven the popularity of lightweight bricks in the last decade. On the other hand, ship repair activities generate sandblasting waste, amounting to 2.5–3 million tons per year, which contains heavy metals and corrosive residues, and is therefore categorized as B3 waste. This study aims to transform sandblasting waste into environmentally friendly partition walls that support earthquake and fire disaster mitigation by formulating lightweight bricks of the Cellular Lightweight Concrete (CLC) type through the modification of foam agents and the substitution of fine aggregates. Initial studies, conducted through interviews at one of the shipyards, revealed an average monthly generation of sandblasting waste of 12,100 kg. This study combines laboratory experiments and a literature review to examine material properties, including gradation, specific gravity, water absorption, and metal content (XRF–TCLP), as well as to evaluate compressive strength, density, and potential applications in earthquake disaster mitigation. The characterization results indicate that the sandblasting waste meets the gradation requirements specified in SNI 03-2834-2000 and passes physical tests according to SNI 03-1970-2008, with heavy metal content (Ba, Zn, Cu) below the threshold set in PP No. 22 of 2021. Lightweight bricks are made with a composition ratio of 1:1 cement and sandblasting waste, and variations in the foam agent range from 5% to 12.5%. The best formula, according to SNI 8640-2018, is obtained at a foam agent content of 5%, resulting in a compressive strength of 7.28 MPa and a density of 1,283.33 kg/m³, which is lighter than concrete blocks and red bricks. From an earthquake mitigation perspective, it was found that lighter material weight contributed to reducing inertial forces and loads on the structure, thereby enhancing resistance to initial collapse and facilitating ease of dismantling during post-earthquake evacuation. These findings indicate that sandblasting waste has the potential to be processed into environmentally friendly alternative construction materials that not only meet technical standards but also contribute to earthquake risk mitigation strategies.